2016
DOI: 10.3390/info7030053
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Software HEVC to AVS2 Transcoding

Abstract: Abstract:The second generation of Audio and Video coding Standard (AVS) is developed by the IEEE 1857 Working Group under project 1857.4 and was standardized in 2016 by the AVS Working Group of China as the new broadcasting standard AVS2. High Efficient Video Coding (HEVC) is the newest global video coding standard announced in 2013. More and more codings are migrating from H.264/AVC to HEVC because of its higher compression performance. In this paper, we propose an efficient HEVC to AVS2 transcoding algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Fuzzy logic controllers (FLCs) have been widely used for MPPT application in the literature [28]- [31]. Every FLC consists of three parts; fuzzification, fuzzy rule tables and defuzzification.…”
Section: Fuzzy Logic Control Based Mppt Methodsmentioning
confidence: 99%
“…Fuzzy logic controllers (FLCs) have been widely used for MPPT application in the literature [28]- [31]. Every FLC consists of three parts; fuzzification, fuzzy rule tables and defuzzification.…”
Section: Fuzzy Logic Control Based Mppt Methodsmentioning
confidence: 99%
“…Nonetheless, a number of interesting transcoding solutions are reported for HEVC into non-ISO standardized coder are reported. For instance, in [10] a HEVC to Audio Visual Standard version 2 (AVS2) transcoder is proposed which decodes the incoming video in multi-stages to make use of HEVC information in the transcoding process. The authors reported speedup in the range of 11 × to 17 × over AVS2 reference software.…”
Section: Literature Reviewmentioning
confidence: 99%